1995
DOI: 10.1111/1523-1747.ep12607031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genetic Association of Human Leukocyte Antigen Class II and Tumor Necrosis Factor-Alpha with Dermatitis Herpetiformis

Abstract: Dermatitis herpetiformis is a chronic subepidermal vesicular autoimmune skin disease characterized by a strong association with the human leukocyte antigen A1-B8-DR3-DQ2 haplotype. Although the strongest major histocompatibility complex association has been shown to be with the DQw2 (DQB1*0201/DQA1*0501) heterodimer, recent evidence has suggested that there may be up to three susceptibility loci within the major histocompatibility complex. Tumor necrosis factor-alpha (TNF-alpha) is a cytokine with a broad rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…11 Alleles at CCR5D32, CCR5 59353, CCR2+190 (V64I), SDF1 3#UTR, and CCR5 59029 were determined by sequence-specific priming. 12 IL4-589 13 and TNFA-1031 14 alleles were assessed by PCR-RFLP using primers described previously.…”
Section: Methodsmentioning
confidence: 99%
“…11 Alleles at CCR5D32, CCR5 59353, CCR2+190 (V64I), SDF1 3#UTR, and CCR5 59029 were determined by sequence-specific priming. 12 IL4-589 13 and TNFA-1031 14 alleles were assessed by PCR-RFLP using primers described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Small studies have been carried out in a variety of conditions. Disease associations have been shown for the TNF -308 alleles and dermatitis herpetiformis (Wilson et al, 1995a) or alopecia areata (Galbraith and Pandey, 1995). In three studies of various forms of psoriasis (Alheresh et al, 1997;Arias et al, 1997;Hohler et al, 1997) all showed significant associations with the TNF -238 alleles, and the latter study (Alheresh et al, 1997) also showed an association with TNF -308 polymorphism.…”
Section: Multiple Sclerosis (Ms) Multiple Sclerosis (Ms) Is Amentioning
confidence: 97%
“…28 In support for a clinical relevance, the À308A allele is associated with a seven-fold increased risk for cerebral complications of malaria 29 and with a worse prognosis and longer disease duration in dermatitis herpetiformis. 30 However, the same marker was not responsible for differential TNFa production induced by standard in vitro stimuli. 31 Although taking into consideration the importance and informativeness of known functional loci in inflammatory genes, it can be assumed that consistent pictures of IL1b, IL6 and TNF genotype-phenotype relationships are yet to emerge.…”
Section: Introductionmentioning
confidence: 98%